Influencing factors of pregnancy-related anxiety in advanced maternal age primigravidas and the development and evaluation of personalized psychological nursing interventions - Gao, Yan; Yang, Lei; Sun, Jingwen; Nan, Yiping; Hou, Li; Li, Xiaomei (Frontiers in Psychiatry, 2025)
BackgroundPrimigravidas of advanced maternal age (AMA) encounter distinct challenges throughout pregnancy and are particularly susceptible to heightened levels of anxiety.ObjectiveTo identify the influencing factors of pregnancy-related anxiety in AMA primigravidas and to develop, implement, and evaluate a personalized psychological nursing intervention.MethodsPhase I involved a cross-sectional survey of 300 AMA primigravidas to identify anxiety-influencing factors. Phase II was a randomized controlled trial (RCT) with 160 AMA primigravidas assigned to either a personalized psychological nursing intervention group or a standard care control group.ResultsPhase I identified key factors influencing anxiety, including perceived pregnancy risks, social support, and self-efficacy. In Phase II, the intervention group showed significantly lower anxiety levels (p < 0.001), improved self-efficacy (p < 0.001), and higher satisfaction with prenatal care (p < 0.01) compared to the control group.ConclusionPersonalized psychological nursing interventions based on identified influencing factors effectively reduce anxiety and improve psychological well-being in AMA primigravidas. Implementation of such interventions in prenatal care could significantly enhance outcomes for this vulnerable population.